2019
DOI: 10.3390/su11164308
|View full text |Cite
|
Sign up to set email alerts
|

Transition towards Sustainability: Adoption of Eco-Products among Consumers

Abstract: Transition to sustainability is a long-term challenge which should also actively engage consumers, as consumption causes environmental stress. In order to understand how consumers adopt eco-products, we conducted an extensive literature review of green consumerism and presented findings of 47 previous research works. In addition, this study’s aim was to explore whether consumers remain only concerned about the environment or whether they actually make a difference. Moreover, we examined gender differences. Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 81 publications
(74 reference statements)
6
58
1
1
Order By: Relevance
“…Our investigation related to the differences in gender are in line with studies of Liobikienė et al (2017) and Hojnik et al (2019), which found that woman behave in a more environmentally friendly way and are more consciousness of eco-labelled products than male consumers. Green purchase behaviour is significantly related to environmentally friendly behaviour.…”
Section: Source: Own Research and Spss Resultssupporting
confidence: 88%
“…Our investigation related to the differences in gender are in line with studies of Liobikienė et al (2017) and Hojnik et al (2019), which found that woman behave in a more environmentally friendly way and are more consciousness of eco-labelled products than male consumers. Green purchase behaviour is significantly related to environmentally friendly behaviour.…”
Section: Source: Own Research and Spss Resultssupporting
confidence: 88%
“…Irianto (2015) confirmed positive attitudes and positive purchasing intentions of women towards green food. Research that covered consumers from Slovenia showed that women expressed more profound concern about the environment and had greater awareness of eco-products than men, even though there were no differences between women and men regarding green purchase intentions (Hojnik et al, 2019). The share of Macedonian women in the green segment is high (Bojkovska et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consumers' awareness of the environment is increasing worldwide. Hence, many companies started to produce and create products that are environmentally friendly and have a smaller adverse effect on the environment (Hojnik et al, 2019). The increasing environmental awareness makes changes in consumers' consuming behavior to purchase more ecofriendly products (Siddique and Hossain, 2018).…”
Section: Relationship Between Environmental Awareness and Product Attitudementioning
confidence: 99%